2009
DOI: 10.1016/j.vaccine.2009.01.128
|View full text |Cite
|
Sign up to set email alerts
|

Rabies DNA vaccine: No impact of MHC Class I and Class II targeting sequences on immune response and protection against lethal challenge

Abstract: Rabies is progressive fatal encephalitis. WHO estimates 55,000 rabies deaths and more than 10 million PEP every year world-wide. A variety of cell-culture derived vaccines are available for prophylaxis against rabies. However, their high cost restricts their usage in developing countries, where such cases are most often encountered. This is driving the quest for newer vaccine formulations; DNA vaccines being most promising amongst them. Here, we explored strategies of antigen trafficking to various cellular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
4

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 52 publications
2
13
0
4
Order By: Relevance
“…This is in agreement with Kaur et al, who reported variation in protective efficacy despite similar magnitude of immune responses. 28 It is possible that cellular immune factors, in addition to RVNA, may also be involved in protection against intracerebral rabies virus challenge. The present study, however, did not evaluate the cellular immune responses to dendriplex vaccination.…”
mentioning
confidence: 99%
“…This is in agreement with Kaur et al, who reported variation in protective efficacy despite similar magnitude of immune responses. 28 It is possible that cellular immune factors, in addition to RVNA, may also be involved in protection against intracerebral rabies virus challenge. The present study, however, did not evaluate the cellular immune responses to dendriplex vaccination.…”
mentioning
confidence: 99%
“…To improve DNA uptake, electroporation has been used and was shown to generate comparable or superior levels of immune responses [102,103]. To increase the immunogenicity and efficacy of DNA vaccines, several approaches have been conducted, including using chemical adjuvants [104,105], co-administrating plasmids expressing cytokines [106,107], modifying the targeted G protein [108,109], increasing the expression level of encoded proteins [94], co-inoculating with a traditional inactivated rabies vaccine [110], and optimizing DNA vaccine formulation, such as through targeted trafficking of a G protein to a lysosome supplemented with adjuvant Emulsigen-D [111,112]. These endeavors have significantly increased the immunogenicity and efficacy of DNA vaccines and extended their potential in preventing and controlling rabies.…”
Section: Other Novel Modalities For Rabies Control and Preventionmentioning
confidence: 99%
“…In this regard, antigen targeting to different cellular processing compartments may improve its presentation by MHC I or MHC II molecules and enhance specific immune response [28][29][30][31][32]. In addition, the secretion of cellular proteins was reported to modulate the immunological responses.…”
Section: Introductionmentioning
confidence: 99%